Preparation for injectable dental anаesthesia (LLC "Endo Press", 2020)
In medicine, performing an injection involves antiseptic preparation of the skin and application of topical anaesthetic prior to the procedure. The studies reviewed show that dentists in Russia ignore them in 70-75% of cases. Dental literature and guidelines published before the 2000s did not contain any information on oral cavity preparation prior to giving injections. Due to introduction of vascular types of anaesthesia, and intraligamental anaesthesia in particular, we suggest considering the following issues: possibility of developing catarrhal and ulcerative gingivitis and potential risk of developing infective endocarditis after vascular injection of an infected anaesthetic. No studies report infective endocarditis as a complication of spongeous anaesthesia (ILA). It is disappointing that the new module in the dental curriculum (2011) «Local anaesthesia and anaesthesiology in dentistry» does not contain any step-by-step oral cavity preparation prior to performing an injection. Based on the findings we obtained in the clinical experiment, domestic and international experience of giving anaesthesia, we have developed the draft clinical protocol.